Modification of Electrode in Dermatosensory Evoked Potential (Indian Journal of Forensic Medicine & Toxicology, 2020)
Somatosensory evoked potential (SSEP) usually done using bipolar surface stimulator of peripheral nerveand recorded by cortical surface or subdermal needle electrodes, in this study we modify an adhesive largesurface area, surface stimulator using the same montage and method then compare the result between them. Wetook nineteen patients of median nerve SSEP, locate and identify the shape of dermatom assigned accordingto text using large square adhesive surface electrode. The same as the shape of dermatom, this is the cathodeelectrode, for the anode, a strip has the same length of the cathode with a width of two centimetres placedbeneath the cathode, the circular ground band between stimulated and recording electrode. The subjectsIn this study prepared for routine SSEP study the result obtained of both study compared using statisticalmethod and we found there was a significant different between two method and the modified as higheramplitude using lesser stimulated threshold but not significant different between latency. That’s happenedbecause we increased the surface area of stimulation which means more the motor nerve was stimulated.
Keywords: Somatosensory, evoked potential, electrode, electrical charge.